Investigating the impact of advertising during economic shocks on firm performance in the hospitality industry. Issue 8 (17th November 2019) - Kim, Taewoo; Choi, Hyunsuk; Song, Chanho; Lee, Myong Jae (MJ)
ABSTRACT: This study examines the impact of advertising to determine whether advertising expenditure after economic shocks is associated with hospitality firm performance. Using the ordinary least squares (OLS) regression models for the earnings response coefficient study, we found that firm performance was positively related to hospitality firms that spent more on advertising immediately after a global financial crisis. Furthermore, this research revealed that long-term performance among hospitality firms was associated with increased advertising expenses after a global financial crisis. These findings have practical implications, providing hospitality industry managers with advertising guidelines to develop resilience during financial setbacks caused by economic shocks.